Interrelationships of fishes. - Greenwood, P. H.; Miles, R.S.; Patterson, Colin (London Academic Press, 1972)
Suppl.1 Zoological Journal of the Linnean on Society, vol.53
Keywords: Fishes--Evolution--Congresses.; Fishes--Anatomy--Congresses.; Fishes--Evolution--Congresses.